Removal of cadmium and chromium using activated carbons developed from lignocellulosic wastes (LACCEI, 2024)
Agroindustrial peanut production in Argentina covers 3% of world demand. The surface area sown exceeds 400000 Ha and is mainly carried out in the Province of Córdoba. This generates a large amount of waste, being the shell the main waste. In the present work, a sample of activated carbon is developed from peanut shells by chemical activation. The activating agent used was orthophosphoric acid and the carbonization of the sample was carried out in an autogenerated atmosphere at a temperature of 450ºC. The study of the textural characteristics of the activated carbon prepared showed an extensive BET specific surface area (1253 m2/g) and a great development of the pore structure with a total volume of 1.01 cm3/g. The morphological study, by means of SEM micrographs, allowed visualizing the pronounced porosity of the material. From the analysis of the pore size distribution it could be determined that the carbonaceous material is of the mesoporous type. The performance of the activated carbon in the adsorption of Cr(VI) and Cd(II) in batch processes was studied. The results showed that the adsorbent material developed presented a good performance in the removal capacity of both pollutants.